Steering column with locking mechanism - L.FEVRE; DUPONT ELODIE (2025)
The subject of the invention is a steering column (10) having a base and a steering mechanism (16), comprising the following components:-a movable bracket (20) which is mounted in a pivotable manner relative to the base (14); -a lower tube (24), which is slidably mounted in the movable support (20); and an upper tube (26) which is slidably mounted in the sliding body (24). According to the invention, the movable support (20) has a lock (30), which has a locked state and an unlocked state, in which the lock holds the sliding body (24) in the axial direction in the moved-out position and in which the lock releases the sliding body (24), the base has a control surface (32), which is designed to cause an unlocking of the locking device (30) when the movable support (20) is pivoted into the moved-in position of the upper part of the movable support (20). 本发明的主题是一种具有底座和转向机构(16)的转向柱(10)，所述转向柱包括以下组件：-可运动的支架(20)，所述可运动的支架以相对于底座(14)可摆动的方式被安装；-下管(24)，所述下管滑动地被安装在所述可运动的支架(20)中；-上管(26)，所述上管滑动地被安装在所述滑动体(24)中。所述可运动的支架(20)具有锁定